Penerapan Model Pembelajaran PBL (Problem Based Learning) Materi Daur Air Pada Pelajaran Biologi - Desvina Dwi Jayanti; Qonaah Nuryan Arif; Meli Marlina (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Learning is a process, an activity and not a result or goal. Learning is not just remembering, but broader than that, namely experiencing. This article discusses how to apply the PBL (Problem Based Learning) learning model in increasing student activity. This research is classified as qualitative descriptive research. In the learning process, students tend to get bored and less interested in the ongoing learning process because the method used is only lectures and is monotonous. Student activity in the learning process also has an important role in learning outcomes. The project based learning learning model is a scientific approach which consists of several stages, including observing, asking, collecting information, reasoning and communicating. Through these various stages students can increase their role in the learning process.